Overdose in young children treated with anti-reflux medications: Poisons enquiry evidence of excess 10-fold dosing errors with ranitidine. (April 2018) - Crawford, C; Anderson, M; Cooper, G; Jackson, G; Thompson, J; Vale, A; Thomas, SHL; Eddleston, M; Bateman, DN
Background: Accidental drug overdose is a common problem in young children. We examined the influence of formulation and dose in enquiries for different gastro-oesophageal reflux disease treatments in children under 5 years to the UK's National Poisons Information Service. Methods: Overdose characteristics with ranitidine, omeprazole or domperidone were compared with those of metoclopramide and the H-1 antagonist chlorphenamine, for the period 1 July 2007 to 30 June 2015. Results: There were a total of 1092 ranitidine, 618 domperidone and 1193 omeprazole cases; 669, 281 and 424, respectively, were single agent enquiries; of these 77% (517) of ranitidine, 52% (145) domperidone and 32% (135) omeprazole cases occurred in children <5 years. In comparison, 17% (34/424) of metoclopramide and 53% (533/1013) of chlorphenamine were <5 years; 79% (410/517) of ranitidine overdose enquiries in children <5 years were under 6 months of age, higher than domperidone (68/145, 47%; p < 0.05), omeprazole (8/135, 6%), chlorphenamine (13/553, 2%) or metoclopramide (1/34, 3%) (all p < 0.01). In children aged <6 months, 101 were 10-fold overdoses, 86 with ranitidine. Conclusions: Tenfold overdoses in children (<5 years) were a feature of ranitidine enquiries, likely due to the high concentration of the syrup. This has relevance to other liquid formulations used for non-licenced indications in young children. Such therapeutic errors cause significant carer anxiety and healthcare utilization. Assistance is needed from manufacturers and legislators in modifying formulation so that drugs can be safely used in young children. Education of prescribers and carers is also needed to reduce the incidence of such errors that cause significant carer anxiety and healthcare utilization.